Analisis Perumusan Strategi Keunggulan Kompetitif Bisnis Pakan Ternak melalui Pendekatan Resource Based View (Studi Kasus PT Mabar Feed - Widiasto, Riza Purbo; Hermawan, Aji; Suprayitno, Gendut (Universitas Brawijaya, Indonesia, 2014)
The aims of this study are identifying and assessing the company resources and the capabilities of the company in which potential to produce a sustainable competitive advantage through resources based view analysis. Besides, it produces the alternative strategies in order to exploiting the resources and capabilities to create a competitive advantage for the company. This research is using qualitative case study method in order to explore and capture the phenomenon on the unit of analysis. The result shows that the company has 22 types of resources and 24 types of capabilities on the value chain activities of companies that have potential as a competitive advantage. The analysis uses the VRIO framework and it gives the results that the company only has a few resources and capabilities that can produces a temporary competitive advantage. Companies can achieve a sustainable competitive advantage by creating the formulation strategy through utilizing and exploiting the resources and capabilities of the companies.